(untitled) (Medico Legal Update, 2021)
In the present study, 70 of patients were 35 males and 35 females were suffering from chronic kidney disease, and 20 of control group. The samples were collected from Specialized Center for Diseases and Kidney Transplant in AL-Sadder Medical City/Najaf Governorate/Iraq, during the period from July till August, 2019. The ages of control and patients ranged 30 to 69 y old. The patients group was divided into subgroup according to the age and gender, Patients without a complete medical record were excluded and those with other diseases were excluded. The present study revealed a significant enhance (p<0.05) inserum PTX3 and SOST levels in CKD compare with control group, while a significant decline (P<0.05) in serum HDL level of CKD in comparison with control group. The result indicated no significant differences (p>0.05) in serum of PTX3 and SOST levels between female and males groups of CLD patients. Also, The results showed a significant increase (p>0.05) in serum PTX3 and SOST levels there was a significant increase(p<0.05)among different groups ages. There is a positive association between PTX3 and SOST concentrations of CKD patients Conclusion: The current study conducted that PTX3 and SOST levels were good markers for diagnosis and detection of chronic kidney disease in both genders the males and females.